Исследование процесса адсорбции 99mТс (VII) на активированном оксиде алюминия - Скуридин В. С. Виктор Сергеевич; Стасюк Е. С. Елена Сергеевна; Варламова Н. В. Наталья Валерьевна; Садкин В. Л. Владимир Леонидович; Рогов А. С. Александр Сергеевич (2011, 2011)
В фонде НТБ ТПУ отсутствует